2005
DOI: 10.3122/jabfm.18.6.478
|View full text |Cite
|
Sign up to set email alerts
|

Current Role of Magnetic Resonance Imaging in Breast Imaging: A Primer for the Primary Care Physician

Abstract: Magnetic resonance imaging (MRI) isMagnetic resonance imaging (MRI) has revolutionized many areas of body imaging. As a noninvasive, nonirradiating imaging tool, interest has steadily been developing as to the specific role of MRI in breast imaging, and whether this modality can assist with early detection and hopefully subsequently decrease the mortality of breast cancer.Mammography has long been used for early detection of and screening for breast cancers. With optimal technique and patient conditions, it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…It has been suggested that MRI is useful for: (1) detecting cancers that are occult clinically and mammographically; (2) assessing lesion size and spread; and (3) differentiating between malignant and benign lesions. [1][2][3][4][5][6][7] Diffusion-weighted imaging has become a common investigation tool and is used extensively in the central nervous system (e.g., for the diagnosis of acute cerebral infarction). 14,15 Recently, DWI has been increasingly applied to breast imaging following development of the parallel imaging technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that MRI is useful for: (1) detecting cancers that are occult clinically and mammographically; (2) assessing lesion size and spread; and (3) differentiating between malignant and benign lesions. [1][2][3][4][5][6][7] Diffusion-weighted imaging has become a common investigation tool and is used extensively in the central nervous system (e.g., for the diagnosis of acute cerebral infarction). 14,15 Recently, DWI has been increasingly applied to breast imaging following development of the parallel imaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that MRI enabled the detection of breast cancer that was occult on mammography and US. [1][2][3][4][5][6][7] Recently, diffusion-weighted imaging (DWI) has been applied increasingly to the body as well the central nervous system. DWI of the breast is expected to have clinical potential because of its high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The reported sensitivity of mammography in the detection of breast cancer ranges from 69% to 90%, and the reported specificity ranges from 10% to 40% 103. Ultrasonography is not included in the National Comprehensive Cancer Network (NCCN) breast cancer screening guidelines.…”
Section: Screening and Surveillancementioning
confidence: 99%
“…It is believed that mammography alones misses between 10% and 30% of all breast cancers. Possible reasons may include density of breast parenchyma and slow growing breast cancers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been used as an adjunct to mammography, with particular value in differentiating cystic from solid lesions and in facilitating guided biopsy of suspicious areas [2].…”
Section: Introductionmentioning
confidence: 99%